1977
DOI: 10.1073/pnas.74.12.5407
|View full text |Cite
|
Sign up to set email alerts
|

Defects of glycosyltransferase activities in human fibroblasts of Pk and p blood group phenotypes.

Abstract: We demonstrate that human fibroblasts of the rare pk phenotype lack globoside, which was identified as the blood group P antigen, and that p cells possess neither globoside nor trihexosyl ceramide, which was identified as pk antigen. Our investigations indicate also that these glycosphingolipid patterns are most likely caused by inherited preferential biosynthetic pathways in the abnormal phenotypes rather than by excess catabolism of the antigens. Evidence is presented that the fibroblasts of pk phenotype lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…These results are consistent with a recent report that Gb4 was induced in response to TNF-α in human umbilical vein endothelial cells (20). Gb4 is the most prominent neutral GSL in human erythrocytes (21) and is an essential structure of blood group P antigen (22). The physiological function of Gb4 in vivo has not been demonstrated, although it has been shown to be an adhesion molecule on epithelial cells for bacteria (23), cancer cells (24), and some toxins (25).…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with a recent report that Gb4 was induced in response to TNF-α in human umbilical vein endothelial cells (20). Gb4 is the most prominent neutral GSL in human erythrocytes (21) and is an essential structure of blood group P antigen (22). The physiological function of Gb4 in vivo has not been demonstrated, although it has been shown to be an adhesion molecule on epithelial cells for bacteria (23), cancer cells (24), and some toxins (25).…”
Section: Discussionsupporting
confidence: 82%
“…The membranes of Pf phenotype also accumulate trihexosyl ceramide and are lacking globoside but do contain the P1-active glycolipid [10,22]. It has also been demonstrated that fibroblasts of p and P$ phenotypes are lacking a-galactosyl and P-N-acetylgalactosaminyl transferase activities, respectively [23].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies later showed the P antigen to be globotetraosylceramide (Gb 4 Cer, globoside, GalNAc␤3Gal␣4Gal␤4-GlcCer), 1 the most abundant neutral glycolipid in the erythrocyte membrane (2) as well as in other mesodermally derived tissues (3,4). Later it was found that human fibroblasts with the P k phenotype were deficient in ␤-N-acetylgalactosaminyltransferase activity (5).…”
mentioning
confidence: 99%